DAMPAK PANDEMI COVID-19 TERHADAP SEKTOR INDUSTRI PARIWISATA: ANALISIS KONJOINT UNTUK MENGUKUR PREFERENSI WISATAWAN BERKUNJUNG KE BANDUNG - Dendi Gusnadi; Bethani Suryawardani; Astri Wulandari; Dandy Marcelino (Jurnal Ilmu Sosial dan Humaniora, 2022)
The tourism industry sector in West Java is the sector most affected since the COVID-19 pandemic. Local and foreign tourist visits to attractions in West Java Province fell by 80% due to this pandemic. The goal of this study is to determine the behavior of tourists in the future, such as the preferences of tourists to visit Bandung after the end of the pandemic. Knowing what tourist preferences are is hoped that tourism businesses will be able to develop appropriate strategies to serve tourists in the future to stimulate local economies and improve living conditions. With a sample size of 400, this study is quantitative and uses the conjoint analysis technique, the gold standard for gauging traveler preferences. The results of this study are that the next 6-12 months will be the right time to revive the image of tourism which has fallen considerably due to the pandemic situation since early 2020. As for the type of tourist tour that can be the primary choice in nature tourism, during a pandemic like now, outdoor activities are very much needed, one of which is to exercise and sunbathe. Travel time of 1-3 days is the preference of tourists who want to visit Bandung, so business people in the tourism sector should consider what types of short tours should be offered to these tourists. Meanwhile, the priority aspect of destinations that prioritize cleanliness are the primary choice for tourists to travel again after the pandemic. Concerning this priority aspect, the company can also promote cleanliness as its main priority.